COMMUNITY HEALTH INTERVENTIONS IN WYANDOTTE COUNTY, KS & THE DEVELOPMENT OF A ONE HEALTH CLINIC WITH COMMUNITY VETERINARY OUTREACH - Mombello, Valerie (My University, 2022)
Local Public Health Departments serve as an integral point of intervention in the numerous community health challenges faced across the state of Kansas. The Unified Government Public Health Department of Wyandotte County, KS enacts many such interventions through its Community Health Division. This project contributed to three interventions of the Community Health Division, each targeting a distinct audience and community health challenge. The first intervention under Tobacco Free Wyandotte exhibited the prevalence of adolescent tobacco use and the dangers of nicotine exposure in youth. Targeted marketing and the addition of flavoring has introduced a new generation of electronic cigarettes to adolescents, with its addictive qualities establishing their use as mainstream. The use of these popular nicotine devices can greatly affect the cognitive and behavioral functioning of adolescents, leading to disruptions in education. In recognition of these dangers, educators and students have formed the Youth Resist Coalition. This project aimed to educate administrators and peer advocates of the need for tobacco cessation interventions in the Wyandotte County school district through an educational infographic to be included in the Youth Resist Coalition Sponsor Toolkit. The second intervention under the Community Health Improvement Plan (CHIP) addressed the needs of justice-involved individuals in Wyandotte County. Following incarceration, justice-involved individuals face countless barriers in their reintegration into society. The CHIP seeks to assist this vulnerable population through providing access to evidence-based programming and pairing individuals with needed resources within the community. Current best practices in recidivism reduction programming can be tailored to specific demographics within the population justice-involved individuals, creating an opportunity for local resource centers to direct each individual to a subset of aid. This project aimed to identify and unite community resources for justice-involved individuals in Wyandotte County through the distribution of a survey canvassing organizations of their available services and capacity. The third intervention under the Infrastructure Action Team explored the implementation potential of the Complete Streets ordinance recently passed in Wyandotte County. Complete Streets legislation prioritizes community health in infrastructure, emphasizing safety, public health, sustainability, and social equity in each design. Each implementation must be tailored to a specific project. As this ordinance is the first of its kind passed in Wyandotte County, there are no directly applicable precedents for implementation. This project aimed to accumulate resources and provide direction for the Infrastructure Action Team as the inaugural Complete Streets project is designed and implemented.
Keywords: public health